Effect of Probiotic Supplementation on Cognitive Function and Metabolic Status in Mild Cognitive Impairment and Alzheimer's Disease: A Meta-Analysis - Li, Xurui; Lv, Chang; Song, Jinxiao; Li, Jianguo (Frontiers in Nutrition, 2021)
Background: Alzheimer’s disease (AD) is a progressive and multifactorial neurodegenerative disease accounting for 80% of dementia worldwide. Objective: To assess the influence of probiotics on cognitive function in patients with mild cognitive impairment (MCI) and AD. Methods: PubMed, Embase and Cochrane Library databases were searched for relevant studies. Results: Six randomized controlled trials involving 462 patients with MCI and AD were included in this meta-analysis. The probiotic administration had favorable effects on homeostasis model assessment–insulin resistance [HOMA-IR; Weighted mean difference (WMD) = 0.34, 95% confidence intervals (95% CI): 0.44 to 0.24, P < 0.001, I2 = 0%], very low–density lipoprotein levels (VLDL; WMD = 3.71, 95% CI: 6.11 to 1.32, P = 0.002, I2 = 57.7%), quantitative insulin sensitivity check index (QUICKI; WMD = 0.01, 95% CI: 0.00–0.01, P = 0.003, I2 = 51%), and triglyceride levels (WMD = 15.65, 95% CI: 27.48 to 3.83, P = 0.009, I2 = 63.4%) in patients with AD. However, after Hartung-Knapp adjustment, all effects were non-significant except for HOMA-IR (MD = -0.34, 95%CI = -0.58 to -0.11). The changes in the Mini-Mental State Examination, repeatable battery for the assessment of neuropsychological status, and other biomarkers of oxidative stress, inflammation, and lipid profiles (high-sensitivity C-reactive protein, malondialdehyde, and total cholesterol) were negligible. Conclusion: The findings suggested that the consumption of probiotics had favorable effects on the HOMA-IR in patients with AD. However, the probiotic treatment did not affect cognitive function, other biomarkers of oxidative stress, and other lipid profiles.